ROLE OF CT CHEST IN EVALUATION OF PULMONARY MANIFESTATIONS OF COVID-19 RECOVERED CASES - AARTI; GUPTA, SARYU; SIBIA, RAMINDERPAL SINGH; GAMBHIR, PUNEET (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Pulmonary manifestations may be seen in a number of coronavirus disease 2019 (COVID-19)-recovered the evidence on post-COVID pulmonary sequelae is still limited. Herein, we aim to assess the role of computed tomography (CT) chest in the evaluation of pulmonary manifestations of COVID-19 recovered cases. Methods: We conducted a hospital-based study in the Department of Radiodiagnosis at Government Medical College and Rajindra Hospital Patiala. It included 182 reverse transcriptase-polymerase chain reaction (RT-PCR)-proven COVID-19 patients after they recovered from the disease with at least one negative RT-PCR test and/or clinical recovery. Clinical data and CT findings in the recovery phase were summarized, and the relationship of different clinical parameters with CT severity scores was analyzed. Results: The mean (±standard deviation [SD]) age of patients was 50.2±14.7 years, and 62.6% of them were males. The mean (±SD) symptomatic-scan interval was 33.05±22.27 days. Pulmonary abnormalities were found in the majority of the cases in the recovery phase, that is, 176 patients accounting for 96.7%, while six patients had normal scans. Bilateral involvement was seen in 169 out of 176 patients. Common CT patterns observed were ground glass opacities (90.34%), reticular pattern (81.82%), interlobular septal thickening (70.45%), linear opacities (90.34% cases), fibrous stripes (78.41% cases), and consolidation (36.93%). The mean (±SD) CT severity score of our study subjects was 16.10±7.95. Patients were also categorized into four groups according to symptomatic scan interval <1 month, 1–2 month, 2–3 month, and >3 months. We found that residual changes were more severe in patients with shorter symptomatic scan interval. Conclusion: COVID-19 patients demonstrate persistent pulmonary abnormalities even after clinical recovery. Hence, follow-up in patients with moderate and severe disease is strongly recommended.